2019
DOI: 10.1136/bmjhci-2019-100025
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of the stacked, synchronised and iconographic timeline-structured electronic patient record in a UK NHS Global Digital Exemplar hospital

Abstract: BackgroundConventional electronic screen visualisation formats, which use tabs, dropdown menus, lists and multiple windows, present huge navigation challenges to health professionals. A unifying and intuitive interface for the electronic patient record (EPR) has been an elusive goal for software developers for decades.MethodsSince 2009, by working in an agile way, we have built and implemented a fully operational and dynamic system, the University Hospital Southampton Lifelines (UHSL), within our clinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This study’s findings complement studies that have shown that data integration, intuitive interfaces, reduced documentation, and fewer manual tasks help reduce user fatigue and decrease burnout. 8,9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study’s findings complement studies that have shown that data integration, intuitive interfaces, reduced documentation, and fewer manual tasks help reduce user fatigue and decrease burnout. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…This study's findings complement studies that have shown that data integration, intuitive interfaces, reduced documentation, and fewer manual tasks help reduce user fatigue and decrease burnout. 8,9 This study was conducted to understand to what extent the Echo Workflow Solution can help the Echo lab in the context of an integrated workflow and what needs to be further improved therefore the findings may be of interest to cardiologists specialized in echocardiography, sonographers, Echo lab management, and researchers. It is important to note that participants of this study in multiple geographical locations practicing in different healthcare systems and with varied patient populations found value in the Echo Workflow Solution.…”
Section: Discussionmentioning
confidence: 99%
“…They retain fundamental clinical and research value long after their immediate clinical utility has passed, as long as they can be readily accessed. We have demonstrated how new life and utility can be brought to electronic cellular pathology records of any age, through 1 importation of the original data files into a modern database 2 ; linking directly into the EPR and specifically into a data visualisation interface and 3 creating access to those files in an appropriate retrieval and visualisation system.…”
Section: Discussionmentioning
confidence: 99%
“…We have created a data framework of stacked, synchronised and subject-specific timelines and dynamic iconographic representation of documents, reports and other clinical events. 2 This methodology permits the interactive display of the entire ‘whole-of-life’ digital record set for any patient on a single screen.…”
Section: Introductionmentioning
confidence: 99%